Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1007/bf00441811
|View full text |Cite
|
Sign up to set email alerts
|

Clastogen-induced fragility may differentiate pancytopenia of congenital dyskeratosis from fanconi anaemia

Abstract: A male infant is reported with congenital dyskeratosis and pancytopenia Zinsser-Engman-Cole. The bone marrow pathology showed similarities to Fanconi anaemia. Ophthalmological complications were vitreous haemorrhage, haemorrhagic cataracta complicata and glaucoma. Spontaneous and diepoxybutane-induced chromosomal fragility was within the range of normal cells but was elevated through induction with 4-nitroquinoline-oxide. These findings are contrasted with those of Fanconi anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
7

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
0
11
0
7
Order By: Relevance
“…This theory is particularly attractive in the present case of DC. If, as many authors postulate, dyskeratosis congenita is a disorder of chromosomal instability [Schneider et al, 1988;Morrison, 1974;Burgdorf et al, 1977;Carter et al, 1979;Pai et al, 1989b;DeBauche et al, 1990;Dokal et al, 1992;Ning et al, 1992;Dokal and Luzzatto, 1994;Scappaticci et al, 1989], it might be speculated that an affected embryo may be particularly prone to postzygotic mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory is particularly attractive in the present case of DC. If, as many authors postulate, dyskeratosis congenita is a disorder of chromosomal instability [Schneider et al, 1988;Morrison, 1974;Burgdorf et al, 1977;Carter et al, 1979;Pai et al, 1989b;DeBauche et al, 1990;Dokal et al, 1992;Ning et al, 1992;Dokal and Luzzatto, 1994;Scappaticci et al, 1989], it might be speculated that an affected embryo may be particularly prone to postzygotic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies in peripheral blood lymphocytes have shown increased chromosomal breaks, rearrangements, and sister chromatid exchanges [Schneider et al, 1988;Morrison, 1974;Burgdorf et al, 1977;Aguilar-Martinez et al, 1988;Pai et al, 1989b;DeBauche et al, 1990]. However, these abnormalities have not been found in all of the cases [Scappaticci et al, 1989;Juneja et al, 1987;Womer et al, 1983;Connor and Teague, 1981;Gutman et al, 1978;Sirinavin and Trowbridge, 1975;Schroeder and Hofbauer, 1975;Inoue et al, 1973].…”
Section: Discussionmentioning
confidence: 99%
“…Burgdorf et al (1977) have reported on the only DC patient found so far with an exces sive frequency of SCEs in his lymphocytes. Schneider et al (1988) have recently reported on a patient with DC w'hose lymphocytes showed excessive chromosome breaks when treated with 4-nitroquinoline-l-oxide. We did not find such a response in SB's lymphocytes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…syndrome explains the corneal perforation, sicca syndrome and uveitis, first reported in this syndrome. [1,3,5,9]. Die Prognose ist ungünstig.…”
mentioning
confidence: 99%
“…Es wurden folgende Augensymptome beschrieben: Tränenpunktverwachsung, Tränenfluss, vesikuläre Konjunktivitis, Ektropium und Trichiasis, Glaskörperblutung, Katarakt, Augenhintergrundsveränderungen mit Cotton-wool-Herden und retinalen Blutungen [4,6,8,9].…”
unclassified